Electrification of Public Transport Bus Fleet: Identification of Business and Financing Models - Grzegorz Dydkowski; Jozef Gnap; Anna Urbanek (Communications - Scientific letters of the University of Zilina, 2021)
The paper presents possible models of electric buses purchase financing, taking into account purchase prices higher now than in the case of traditional buses. During the research, the solutions used on several continents and in many countries were analysed, including the USA, China and many European countries. The qualitative research methods were used, focusing less on the describing and dimensioning the current state and more on creating and presenting theories and the implementation proposals themselves. As a result, it also allowed to include issues related to applicability and implications of formulated solutions for managerial practice.